Pengaruh Kepuasan Kerja, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada Dinas Pekerjaan Umum Perumahan dan Kawasan Permukiman (DPUPKP) Kabupaten Kulonprogo (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of job satisfaction, work motivation, and work discipline on employee performance, both partially and simultaneously, at the Public Works, Housing and Settlement Areas Office (DPUPKP) of Kulon Progo Regency. The method used is a quantitative approach with data collection techniques through questionnaires distributed to 80 respondents using purposive sampling technique. Data analysis was carried out by testing validity, reliability, classical assumptions, and multiple linear regression using SPSS 24. The results showed that partially, job satisfaction, work motivation, and work discipline each had a positive and significant effect on employee performance. Simultaneously, the three independent variables also have a positive and significant effect on performance. These findings reinforce the importance of managing internal factors such as satisfaction, motivation, and discipline to improve the effectiveness of employee performance in public sector organizations.